Effect of Channeling Agents on the Release Profile of Theophylline from METHOCEL K4M Based Matrix tablets - Razzak, Md Shaikhul Millat Ibn; Khan, Ferdous; Khan, Md Ziaur Rahman; Fatema, Kanij; Islam, Muhammed Shahidul; Reza, Md Selim (Dhaka University Journal of Pharmaceutical Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The present study was undertaken to investigate the effect of channeling agents on the release profile of Theophylline from METHOCEL K4M based matrix systems. Matrix tablets of Theophylline using METHOCEL K4M were prepared by direct compression process. METHOCEL K4M polymer is hydrophilic in nature. NaCl and PEG 1500 were used as channeling agents. Drug release study was evaluated for eight hours using USP 22 paddletype dissolution apparatus using distilled water as the dissolution medium. The release mechanisms were explored and explained with zero order, Higuchi and Korsmeyer equations. The release rate, extent and mechanisms were found to be governed by channeling agent type and content. Higher channeling agent content (42.49%) in the matrix increased the rate and extent of the drug release because of increased porosity in the tablet matrices, at lower channeling agent (19.76%) level, the rate and extent of drug release was decreased and in absence of channeling agents these were least. NaCl ensures maximum release of drug from low viscosity grade METHOCEL K4M than PEG 1500 when other parameters were kept constant. It was found that type and amount of channeling agent significantly affect the time required for 50% of drug release (T50%), percentage drug release at 8 hours, release rate constant (K) and diffusion exponent (n). Kinetic modeling of dissolution profiles revealed drug release mechanism ranges from diffusion controlled or Fickian transport to anomalous type or non-Fickian transport, which was mainly dependent on the presence of type and amount of channeling agent. These studies indicate that the proper balance between a matrix forming agent and a channeling agent can produce a drug dissolution profile similar to a theoretical dissolution profile. Key words: Channeling agent, Theophylline, Release Profile, Methocel K4M DOI = 10.3329/dujps.v7i1.1214 Dhaka Univ. J. Pharm. Sci. 7(1): 27-32, 2008 (June)